Precipitation characterization using a disdrometer at the AlexanderVon Humbolt meteorological observatory - Vílchez Gutarra, Antonio (2025)
The objective of this study was to characterize the precipitation recorded at the Alexandervon Humboldt Meteorological Observatory (OVH), located at the La Molina National Agrarian University in Lima, Peru, using a Thies Clima laser disdrometer. The monitoring period was from June 2, 2021, to March 20, 2022. Drop size distribution (DSD), terminalfall velocity, weighted mean diameter (Dm), and reflectivity (Z) were analyzed. The data obtained were compared with records from a Costa rain gauge and datafrom the Davis automatic weather station. During the winter of 2021, precipitation was classified as stratiform, with drop diameters between 0.188 and 1.125 mm. In the summer of 2022, events with droplets up to 2,750 mmwere recorded, associated with stratiform-convective and convective rainfall. The results show seasonal differences in precipitation microphysics, with implications for the calibration of weather radars.